PENGARUH POLA ASUH ORANG TUA DEMOKRATIS TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA KELAS VII SMPN 1 SITUBONDO - Irma Noervadila; Anisa Meiliana (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2019)
Proper education and care for children will result in the birth effect of achieving children. Therefore, one of the most important things parents do is to know what principles need to be adhered to in order for parents to succeed in educating children and also how to successfully educate children, including parents who have little time to educate his children. Based on the problems above, the authors are interested to make the title "The Effect of Parenting Democratic Parents Against Students' Learning Outcomes in Mathematics Subject Class VIII in SMP Negeri 1 Situbondo Lesson Year 2017/2018". The issues raised are whether the influence of parenting patterns of democratic parents to the results of learning mathematics students (class VIII) SMPN 1 Situbondo academic year 2017/2018. The method used in this study is a quantitative method in which the studied is whether or not the influence of parenting patterns democratic parents to student learning outcomes. Technique of data collecting through observation, questionnaire, and documentation. The result of research indicate There is positive and significant influence of parenting pattern of democratic parent to student's learning result on mathematics subject (SMP Negeri 1 Situbondo 2017/2018) shown by rtabel price for significance 5% of 0.151, Price rH calculated 0.613. So rHitung bigger than rTabel (0,613> 0,151) and value 0,613 consulted with interpretation table which lies between 0,60 - 0,799 which mean level influence of parenting pattern of democratic parent toward result of student learning is strong influence